Cold capitosaurs and polar plagiosaurs: new temnospondyl records from the upper Fremouw Formation (Middle Triassic) of Antarctica. Issue 4 (4th July 2021) - Gee, Bryan M.; Sidor, Christian A.
ABSTRACT: The upper Fremouw Formation (Middle Triassic) of Antarctica preserves a diverse record of temnospondyls, with three species currently recognized. To date, all of the described material belongs to a single clade, Capitosauria. Our reanalysis suggests that cursory historical reports suggesting the presence of a benthosuchid (Trematosauria) are in error. Here we report substantial amounts of hemimandibular material of large-bodied temnospondyls from the upper Fremouw Formation. All seven specimens, including the historic material attributed to Trematosauria, exhibit features indicative of capitosaurian affinities. These specimens represent a notable expansion in the physical and conceptual body of temnospondyl material known from the Fremouw Formation, although they cannot be definitively associated with any of the three previously named Antarctic species in the absence of skeletal overlap. In addition, all of the specimens come from large-bodied individuals (i.e., skull lengths exceeding 70 cm), which likely reflects a taphonomic filter created by the high-energy channel lag deposition of the fossiliferous horizon of the upper Fremouw Formation. We also report the first occurrence of a non-capitosaur, an interclavicle belonging to a plagiosaurid. This represents only the third occurrence of Plagiosauridae in southern Pangea during the Triassic, in contrast to a much richer record of this clade in northern parts of the supercontinent and a rich record of the closely related brachyopids in the southern hemisphere. Together with the continued absence of trematosaurs in Antarctica, the plagiosaurid record hints at nuances in the distribution of cosmopolitan clades patterns that are tied to presently unrecognized ecological and physiological differentiators.